CONTENT ANALYSIS MEDIA KEBIJAKAN DAN CITRA PEMERINTAH DALAM SURAT KABAR TAHUN 2017 - Syarif Budhirianto; Noneng Sumiaty (Dialektika, 2018)
Media newspapers as a messenger to the public has a media agenda and policy agenda in the public interest. The problem is how the newspaper media presents the agenda setting against the current government policy reporting program, as well as how the image and attitude of media alignments. This study uses quantitative analysis with the agenda setting approach. The result of the analysis shows that the agenda of government program and government policy is more related to the rubric of development of society (human development dimension) in accordance with the principle of “ nawacita” which proclaimed by the government, where the element of proximate of the territory is more dominant than the national news. Media news frames have shaped the imagery that can pioneer the change of public opinion and able to make the image formation of a person figure, governmental institution. While the attitude of media alignments on newstone or tone of news is supportive of government policy.